The role of phytohormones in controlling heat stress responses during wheat anther development - Dale, Matthew (2021)
Cereal crops are highly vulnerable to heat stress. Pollen development is particularly susceptible to high temperatures, with prolonged periods of exposure resulting in male sterility and yield loss. With global temperatures set to rise, yield losses are predicted to increase, warranting further investigation into the role of phytohormones in controlling wheat reproductive development and responses to abiotic stress. Various phytohormones have important roles in regulating many aspects of plant development, in particular pollen development and are also implicated in regulating heat stress responses. This project aimed to investigate the role of phytohormones in wheat development and the heat stress response. A stable heat stress assay was initially developed specific for hexaploid wheat var. Cadenza. It was found that conditions of 4 days at 33/26°C d/n 80% humidity was enough to induce a significant loss of grain set when the stress was applied at meiosis or unicellular pollen stages. Utilising this assay, an RNAseq and global hormone analysis was performed on accurately staged anthers after either control or heat stress conditions. The results reveal the complex interplay of phytohormones in controlling pollen development, the changes that occur in response to heat treatment and the genes underlying these changes in accumulation. The reverse genetics approach of TILLING was used to identify gain-of-function mutants which are insensitive to auxin and ethylene in Cadenza. Auxin-insensitive Aux/IAA mutants showed partial male sterility and increased sensitivity to heat stress, in addition to striking defects in lateral roots, root hairs and agravitropism. This project defines an optimised heat stress assay for Cadenza which can be applied to investigating the heat stress response using reverse genetics or endogenous application of hormones. It also demonstrates an application of TILLING as a method to dissect complex signalling pathways and determine their role in development and abiotic stress tolerance of hexaploid wheat.